Mild and Efficient One-Pot Synthesis of Diverse Flavanone Derivatives via an Organocatalyzed Mannich-Type Reaction - Vuppalapati, Srinivasu V. N.; Xia, Likai; Edayadulla, Naushad; Lee, Yong Rok (Synthesis, 2014)
A facile ethylenediamine diacetate (EDDA)-catalyzed one-pot synthesis of biologically interesting flavanone derivatives from 2-hydroxyacetophenones, aromatic aldehydes, and aniline via a Mannich-type reaction is described. This synthetic method provides a rapid access to biologically interesting flavanone derivatives. To demonstrate this method, several biologically interesting natural products bearing a flavanone moiety were synthesized as racemates.
Keywords: aldehydes; ketones; Mannich bases; Michael addition; cycloaddition